2014
DOI: 10.1007/s10103-014-1602-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of low-level laser therapy on repair of the bone compromised by radiotherapy

Abstract: Radiotherapy (RDT) is commonly used for cancer treatment, but high doses of ionizing radiation can directly affect healthy tissues. Positive biological effects of low-level laser therapy (LLLT) on bone repair have been demonstrated; however, this effect on surgical defects of bone previously compromised by radiotherapy has not been evaluated. The aim of this study was to investigate the influence of LLLT (λ = 830 nm) in femur repair after ionizing radiation. Twenty Wistar rats were divided into four groups: co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
10

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 37 publications
0
10
0
10
Order By: Relevance
“…The 30 Gy used in the present study was based in previous studies, which showed that a single high dose of IR led to bone damage, which allowed the effect of irradiation on bone to be evaluated [3, 21]. The fractionated irradiation protocol, recommended for use in human radiotherapy, is complex to perform in animal models.…”
Section: Discussionmentioning
confidence: 99%
“…The 30 Gy used in the present study was based in previous studies, which showed that a single high dose of IR led to bone damage, which allowed the effect of irradiation on bone to be evaluated [3, 21]. The fractionated irradiation protocol, recommended for use in human radiotherapy, is complex to perform in animal models.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, an in vivo study found that PBM was not able to reverse RT-induced bone damage [97]. To our knowledge, there are no clinical studies on the effects of PBM for RT-induced jaw osteonecrosis.…”
Section: Pbm For the Management Of Orofacial And Neck Complications Omentioning
confidence: 99%
“…1 Compared to laser, NIR LED light has gained more attention for its ability to activate anti-in°ammatory processes and is now widely used in veterinary medicine to treat sprains, bone fractures, and to speed the healing of wounds. 3 Over the last 10 years, there has been a lot of studies focusing on whether the transcranial NIR LED light has a regulatory e®ect on electrical activity in the brain, and results from these studies have shown the neuromodulatory e®ect of transcranial NIR. 4 Nevertheless, the light-source type is not the only parameter that must be considered when using PBM.…”
Section: Introductionmentioning
confidence: 99%